PEMANFAATAN POJOK BACA KELAS GUNA MENINGKATKAN MINAT BACA PESERTA DIDIK DI SMPN 20 KOTA TANGERANG - Maharani, Selvina; Hindun, Hindun (Pascasarjana, Universitas Negeri Gorontalo, 2023)
The class reading corner to increase students' interest in reading at SMPN 20 Tangerang City is one of the programs to increase students' interest in reading. The School Literacy Movement (GLS) must be optimized by utilizing the reading corner located in every corner of the classroom and school. With the reading corner, students are expected to be able to make reading a habit so as to form a character of curiosity and thirst for information or knowledge. Reading culture is one of the efforts to educate the nation's generation. The reading corner must also be made as attractive as possible so that students feel comfortable and do not feel bored seeing it. The books in the reading corner should also be varied and not only contain fiction stories.